2013
DOI: 10.1001/jamainternmed.2013.7430
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Monoclonal Antibodies Against Tumor Necrosis Factor Used in Chronic Immune-Mediated Inflammatory Conditions

Abstract: IMPORTANCE Knowledge of the immunogenicity of biologic agents may be helpful for the development of strategies for treatment of chronic immune-mediated inflammatory diseases. OBJECTIVE To summarize the influence of antibodies against biologic agents (AABs [seropositivity]) on efficacy and safety in immune-mediated inflammatory diseases. DATA SOURCES MEDLINE, EMBASE, Cochrane Library, and the Web of Knowledge were searched for articles published in English, Spanish, French, Italian, or Portuguese between 2000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 81 publications
3
74
1
3
Order By: Relevance
“…Etanerept does not give rise to the presence of anti-drug antibodies [74]. A metaanalysis of these studies showed a relationship between the presence of antibodies and infusion reactions on infliximab and hypersensitivity reactions on adalimumab [75]. Presence of antibodies is lower when the drugs are combined with methotrexate or azathioprine.…”
Section: Sheets For the Presentationmentioning
confidence: 99%
“…Etanerept does not give rise to the presence of anti-drug antibodies [74]. A metaanalysis of these studies showed a relationship between the presence of antibodies and infusion reactions on infliximab and hypersensitivity reactions on adalimumab [75]. Presence of antibodies is lower when the drugs are combined with methotrexate or azathioprine.…”
Section: Sheets For the Presentationmentioning
confidence: 99%
“…Метаанализ исследований, проведенных у больных РА, ювенильном идиопатическом артритом, ВЗК, АС, Пс, ПсА и другими СпА, в которых пациенты использовали хотя бы 1 ГИБП и в которых получены данные о АТП (данные 60 статей или тезисов, 13 982 больных), подтвердил негативное влияние АТП на эффективность иФНОα (хотя интерпрета-ция этих данных затруднительна из значительной неодно-родности групп больных); при АС в большинстве исследо-ваний не продемонстрировано достоверной разницы в эф-фективности терапии у серопозитивных и серонегативных по АТП пациентов, показана связь между наличием АТП и развитием реакций гиперчувствительности [99]. Заключение 1.…”
Section: ч а с т о т а о б р а з о в а н и я а н т и т е л к и н ф и unclassified
“…Продолжение исследований иммуногенности ГИБП и путей ее преодоления позволят проводить персонифици-рованную терапию при ревматических заболеваниях [99]. …”
Section: ч а с т о т а о б р а з о в а н и я а н т и т е л к и н ф и unclassified
“…The concerns currently raised against biosimilar products are their efficacy, safety profile including immunogenicity, indication extrapolation, interchangeability, long-term effects and naming [2,4,[11][12][13][14][15]. Among the many safety issues, there is a major concern whether immunogenicity may affect the adverse events, infusion or injection site reaction, hypersensitivity, pharmacokinetic profile, pharmacodynamic profiles or clinical efficacy [12].…”
mentioning
confidence: 99%
“…Among the many safety issues, there is a major concern whether immunogenicity may affect the adverse events, infusion or injection site reaction, hypersensitivity, pharmacokinetic profile, pharmacodynamic profiles or clinical efficacy [12]. Recent data have shown that there has been no further increase in the antidrug antibody positive rate after 6 months of treatment, and that the positive rate was comparable between CTP-13 and the reference agent [11,13].…”
mentioning
confidence: 99%